INTEGRATED MARITIME DOMAIN INFORMATION AWARENESS - Sumali Morapitiya (PREPARE@u® | IEI Conferences, 2021)
The centralized maritime domain awareness information system is the most important and effective factor to the country covered by the sea. This paper presents detailed information on the implemented Automatic Identification System (AIS) network used to collect the data using the central point and the selected 13 points in the whole over the country. Further, using this system collecting the ships and crafts plying the waters around the island can be viewed through a single interface. There are 14 outputs of the AIS system and can grab all details from 13 points to the central point.  The implemented system is low cost and reduces the complexity of collecting information at a central point. The implemented system is more beneficial to the naval parties and the port authority.